(3GdUMjaI GdYdhjI hGdJMaI GdeJVhjIs - (3GdSeGgjLj, GdHMQGfj, YHO Gddg Hf UGdM Hf LeYI Hf TYHGf, J (B1135 (3g`s
(3ChdgG (B:s
(3GdMeO ddg ???Efj PGcQ aj gPg GdUMjaI eG UMJ YfOj QhGjJg hKHJ dOj ELGRJg ef GdOYhGJ GdhGQOI Yf SjO GdhUjjf hUahI GdeQSdjf Zdj Hf CHj WGdH CejQ GdeDefjf (B...s
(3BNQgG (B:s
... (3heG GaJQVJ Ydj aGMJedg Edi ef ChLHJ Mbhbg ef GdBHGA hGdCegGJ hGdENhI hGdCNhGJ hGZaQ dj hdge eY GdeDefjf hGdeDefGJ Gfc bQjH eLjH (B...(3hbO hGab GdaQGZ hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\92s
(3EjVGM Gdecfhf (B2\65s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds